Ballistic testing and theoretical analysis for perforation mechanism of the fan casing and fragmentation of the released blade. (May 2016) - He, Qing; Xie, Zhi; Xuan, Haijun; Hong, Weirong
Highlights: Ballistic tests using stiffened and plate targets impacted by blade-like and cylindrical projectiles were conducted. The targets and the projectiles were with the same material Ti-6Ai-4V. Fragmentation of the blade-like projectile was observed, leading to the change of the failure mode of the target and a much higher ballistic limit. Fragmentation on projectile nose is theoretically analyzed, and the influencing factors such as the critical thickness of the target and the critical impact velocity of the projectile are derived with calculating formulas. A new dishing energy calculating method was proposed for a plate normally impacted by an arbitrary cross-section projectile. Effects of both the casing structure and the fragmentation of the blade on aeroengine casing containment capability are discussed. Abstract: Ballistic tests with plate and stiffened targets impacted by cylindrical and blade-like projectiles were conducted using compressed gas gun to investigate the perforation-resistance performance of aero-engine fan casing during a blade-out event. It was observed that for the plate target impacted by the blade-like projectile, fragmentation on the projectile nose occurred and the targets were failed by petaling; but for the other combinations, the main failure mode of the targets was plugging and the projectiles were intact except in cases when the blade-like projectile hit the stiffeners. Due to the distinct failure mode, ballistic limit for the plate target impacted by the blade-like projectile was much higher. To analyze the perforation resistance of the target, the energy absorption modes were classified and described with analytical models. A new dishing energy calculating method was proposed for a plate normally impacted by an arbitrary cross-section projectile. The energy absorbed by each mode and the ballistic limits for the plate target were calculated using these analytical models. It was found that fragmentation of the projectile led to a larger amount of dishing energy. The formation conditions of the fragmentation on projectile nose were theoretically analyzed, and the influencing factors for the fragmentation such as the critical thickness of the target and the critical impact velocity of the projectile were derived with established formulas. The theoretical analysis agreed well with the test results. It is argued that if the target is thicker than the critical thickness and the initial velocity of the projectile is larger than the critical impact velocity, fragmentation on projectile nose will occur, failure mode of the target will change to petaling, and the perforation resistance of the target will be significantly enhanced.